Comparison of Integrated and Conventional Production of Young Nonbearing Apple Orchards - Borovinova, Maria; Iliyana, Ivanova (Acta Agraria Debreceniensis, 2004)
The large number of pesticide applications in apple orchards creates serious problems with pesticide residues and their side effects on beneficial organisms, the environment and human health. This is the reason behind the search for new systems for apple protection. The investigations were made in apple orchards of the Institute of Agriculture at Kyustendil, during the period from 1997-1999. Three scab resistant cultivars grafted on rootstocks MM106 were planted in 1996. The orchard was divided into four plots. Two plots were treated as „conventionally” and the other two were treated as „integrated” according to the general principles, rules and standards of integrated apple production. The key disease during the experimental period was powdery mildew, which can be controlled only with pruning of infected clusters and shoots during the first three years after planting. The key pests in the orchard during the nonbearing period were the green apple aphid and San Jose scale. In the integrated plant protection system, it is possible to reduce the number of insecticide treatments depending on the density of the main pests.